Quantitative Analysis of Diffusion-Restricted Lesions in a Differential Diagnosis of Status Epilepticus and Acute Ischemic Stroke - Machegger, Lukas; Bosque Varela, Pilar; Kuchukhidze, Giorgi; Steinbacher, Jürgen; Öllerer, Andreas; Prüwasser, Tanja; Zimmermann, Georg; Pikija, Slaven; Pfaff, Johannes; Trinka, Eugen; Mc Coy, Mark (Frontiers in Neurology, 2022)
Abstract Background and Purpose: Distinction between acute ischemic stroke (AIS) and status epilepticus (SE) on MRI can be challenging as restricted diffusion may occur in both conditions. In this study, we aimed to test a tool, which could help in differentiating AIS from SE when restricted diffusion was present on MRI. Materials and Methods: In diffusion-weighted images (DWI) with a b-value of 1000 and in apparent diffusion coefficient (ADC) maps, we compared the ratios of intensities of gray values of diffusion-restricted lesions to the healthy mirror side in patients with AIS and SE. Patients were recruited prospectively between February 2019 and October 2021. All patients underwent MRI and EEG within the first 48 hours of a symptom onset. Results: We identified 26 patients with SE and 164 patients with AIS. All patients had diffusion-restricted lesions with a hyperintensity in DWI and ADC signal decrease. Diffusion restriction was significantly more intense in patients with AIS compared to patients with SE. The median ratios of intensities of gray values of diffusion-restricted lesions to the healthy mirror side for DWI were 1.42 (IQR 1.32-1.47) in SE and 1.67 (IQR 1.49-1.90) in AIS (p<0.001). ADC decrease was more significant in AIS compared to SE with median ratios of 0.80 (IQR 0.72-0.89) vs. 0.61 (IQR 0.50-0.71), respectively (p<0.001). A cut-off value for ratios of DWI signal was 1.495 with a sensitivity of 75% and a specificity of 85%. Values lower than 1.495 were more likely to be associated with SE and higher values - with AIS. Cut-off value for ADC ratios was 0.735 with a sensitivity of 73% and a specificity of 84%. Values lower than 0.735 were more likely to be associated with AIS and higher values - with SE. Conclusion: Diffusion restriction and ADC decrease were significantly more intense in patients with AIS compared to the SE. Therefore, quantitative analysis of diffusion restriction may be a helpful tool for differentiating between AIS and SE when restricted diffusion is present on MRI.